Nutritional assessment of rubber seed meal with broiler chicks - Nwokolo E; Bragg D; Sim J
In Canada proximate component, mineral, amino acid and fatty acid composition of rubber seed meal were determined, using whole and defatted rubbr seed meals. A growth trial with broilers in which 50;of dietary protein was supplied by rubber seed meal (RSM), soya bean meal (SBM), groundnut meal (GNM) or by combinations of these ingredients with RSM, was conducted. Rubber seed meal had a very high content of K, a high content of P and Mg and a moderate content of Ca. Zn and Fe contents were very much higher than usually encountered in oil seed meals. RSM was low in lysine, the sulphur amino acids, and many other amino acids, in comparison with soya bean meal. Average amino acid availability was moderately high (80.3;) but less than 93.3;in soya bean meal. Rubber seed oil had a high content of polyunsaturated fatty acids, with an exceptionally high level of linolenic acid. Broiler chicks fed RSM diets performed significantly less well than those fed SBM diets. Performance on RSM diets was similar to that on combinations.
Keywords: Broiler chicken; Canada; Chemical composition; Feed intake; Nutritive value; Rubber seed meal; Waste utilization